Effects of operational and environmental parameters on the performance of a solar photovoltaic-thermal collector. (1st February 2020) - Parthiban, Anandhi; Reddy, K.S.; Pesala, Bala; Mallick, T.K.
Highlights: Three-dimensional thermal model for water based solar PV/T. Temperature-dependent electrical efficiency of solar PV is considered. Impact of operational and environmental parameters is studied. Three-dimensional temperature distribution across various layers is obtained. Techno-economic analysis is performed. Abstract: A steady, three-dimensional model considering all the layers of a solar photovoltaic-thermal collector with sheet and tube heat exchanger is developed. The model takes the solar heat loading as the thermal input to estimate the temperature distribution in the collector for variation in incident radiation, ambient temperature, wind velocity, flow rate and inlet water temperature. Based on the numerical results, the parameter that highly influences collector performance is the coolant mass flow rate. For the range of flow rates considered, a maximum efficiency of 93.01% is obtained for 44 LPH. Further, a techno-economic comparison of the photovoltaic-thermal system is made with a photovoltaic system and a flat plate thermal system. The increase in electrical efficiency of the photovoltaic-thermal system is only marginal to that of the photovoltaic system but the overall efficiency of the former is high. The annual cost of energy that the photovoltaic-thermal system can supply is found to be 0.13 USD/kWh from economic analysis.